2018
DOI: 10.3389/fphys.2018.00187
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxygen Enrichment on Cardiorespiratory and Neuropsychological Responses in Workers With Chronic Intermittent Exposure to High Altitude (ALMA, 5,050 m)

Abstract: It is estimated that labor activity at high altitudes in Chile will increase from 60,000 to 120,000 workers by the year 2020. Oxygenation of spaces improves the quality of life for workers at high geographic altitudes (<5,000 m). The aim of this study was to determine the effect of a mobile oxygen module system on cardiorespiratory and neuropsychological performance in a population of workers from Atacama Large Millimeter/submillimeter Array (ALMA, 5,050 m) radiotelescope in the Chajnantor Valley, Chile. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
5
16
0
Order By: Relevance
“…4). In fact, these findings are in line with the findings from Moraga et al (2018), who reported beneficial effects of oxygen supplementation among ALMA workers leading to improvements in some of the assessed cognitive domains. Our findings, together with the ones reported by Moraga et al, support the long-standing advocacy for oxygen enrichment in high-altitude workstations as well as for permanent dwellers, to improve overall performance (West 2016a, b).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…4). In fact, these findings are in line with the findings from Moraga et al (2018), who reported beneficial effects of oxygen supplementation among ALMA workers leading to improvements in some of the assessed cognitive domains. Our findings, together with the ones reported by Moraga et al, support the long-standing advocacy for oxygen enrichment in high-altitude workstations as well as for permanent dwellers, to improve overall performance (West 2016a, b).…”
Section: Discussionsupporting
confidence: 90%
“…The altitude of OSF (2900 m), where we took the first measurements, is already an elevation that can affect performance. Previous studies have shown that ALMA workers do have impairments in cognitive functioning, which improve with oxygenation supplementation (Moraga et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations